Grant : a biography - McFeely, William S. (New York : Norton, 1982)
Chronicles the life of Ulysses S. Grant, the Ohioan who became the leader of the Union Army and later the president
Crowds and families -- Cadetship and courtship -- The Mexican War -- A soldier between wars -- Galena -- Escaping from the ordinary -- Warriors -- Battles -- Shiloh -- Vicksburg -- Chattanooga -- Washington and the Wilderness -- Petersburg -- Peace -- "On the Mexico" -- After the war -- The rising man -- The president and his cabinet -- Original occupants of this land -- A Friday and a friend -- England and Santo Domingo -- Democracy -- Greatness -- Wedding and whiskey -- Waifs -- Around the world -- Grant & Ward -- To write a book: to be a man
"First published as a Norton paperback, 1982."
BIBINDX
Keywords: Grant, Ulysses S. -- 1822-1885; Presidents -- United States -- Biography; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- Politics and government -- 1869-1877